2010
DOI: 10.1007/s00192-009-1032-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures and definition of cure in female stress urinary incontinence surgery: a survey of recent publications

Abstract: Outcome measures used to evaluate success of anti-incontinence procedures lack consensus and comparability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 11 publications
1
33
2
1
Order By: Relevance
“…It would seem that most clinical studies now incorporate some degree of PROs as a measure of assessment [18]. However, it remains unclear how PROs are being used and what role they play in determining overall study end points.…”
Section: Current Use Of Patient-reported Outcomes In the Pelvic Floormentioning
confidence: 98%
See 1 more Smart Citation
“…It would seem that most clinical studies now incorporate some degree of PROs as a measure of assessment [18]. However, it remains unclear how PROs are being used and what role they play in determining overall study end points.…”
Section: Current Use Of Patient-reported Outcomes In the Pelvic Floormentioning
confidence: 98%
“…[18] performed a systematic literature review of published studies involving surgical treatment of female stress UI to review the use of outcome measures. A total of 91 studies published between 2005 and 2006 were analyzed, and most (96%) used either subjective outcome measures only (33%) or both objective and subjective measures (63%) in their outcome assessments.…”
mentioning
confidence: 99%
“…Ninety-six percent of recent articles reporting on surgical outcomes for female stress incontinence use subjective outcome measurements [1]. Questionnaires are useful for research purposes and shorter questionnaires in particular can be integrated into routine clinical practice to complement history taking, enhance effective communication, and, in some cases, guide treatment efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal was to (1) create Spanish versions of four important pelvic floor disorders questionnaires using culturally sensitive methods recommended by modern cross-cultural researchers and (2) validate these Spanish questionnaires for clinical and research use in the Spanish-speaking US and Latin American populations.…”
Section: Introductionmentioning
confidence: 99%
“…Castillo et al [2] analyzed 91 surgical series of SUI and reported that 33% of these studies used only subjective measures, 4% only objective measures, and 63% both objective and subjective measures, for the definition of "cure." Not surprisingly, therefore, the cure rates of the same surgical procedure for SUI differed among these studies.…”
mentioning
confidence: 99%